PERLINDUNGAN HUKUM TERHADAP PENGUNGKAP FAKTA (WHISTLEBLOWER) DALAM HUKUM POSITIF DI INDONESIA - Rosmawati, Rosmawati; R, Mukhlis; Putri, Adi Tiara (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Legal protection is a form of service that must be provided by the government to provide a sense of security to every member of society as well as to whistleblowers. Whistleblowers have a big risk when disclosing a crime, such as threats in the form of terror, loss of life, and are likely to harm themselves related to the information they provide which leads to defamation and back-reporting. In positive law in Indonesia, it does not specifically regulate the protection of whistleblowers, the regulations are implicitly contained in Law Number 13 of 2006 concerning Protection of Witnesses and Victims, Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection Witnesses and Victims, followed by Circular Letter of the Supreme Court (SEMA) Number 4 of 2011 concerning the Treatment of Whistleblowers and Offender Witnesses who collaborate (Justice Collaboration) in Certain Criminal Acts. Even though it has been regulated in several laws and regulations, this does not guarantee protection for whistleblowers in disclosing criminal acts that they know about without fear of retaliation against boththemselves and their families.This study uses a normative juridical approach to find legal norms and norms that constitute criminal law policy in formulating whistleblower protection, using secondary data as a data source. Methods of data collection in a normative juridical approach in this study using literature study techniques. The purpose of this study is to determine the guarantee of legal protection against whistleblowers, to know the weaknesses of legal protection guarantees against whistleblowers, and to know the idea of legal protection for whistleblowers in positive law in Indonesia.From this research it can be concluded that the guarantee of protection against whistleblowers is still lacking due to criminalization or back reporting of whistleblowers. There are no specific regulations governing the protection of whistleblowers where the regulations are still concise, partial, sectoral and scattered in several regulations. The number of institutions that regulate the receipt of reports from a whistleblower with the respective potentials of authority will cause their own problems. Therefore, there is a need for renewal of legal substance, renewal of legal and institutional structures in legal protection for whistleblowers.Keywords : Guarantee - Legal Protection - Whistleblower